Developing a surface acoustic wave-induced microfluidic cell lysis device for point-of-care DNA amplification - ŞİŞMAN, ALPER (My University, 2023)
We developed a microchip device using surface acoustic waves (SAW) and sharp-edge glass microparticles to rapidly lyse low-level cell samples. This microchip features a 13-finger pair interdigital transducer (IDT) with a 30-degree focused angle, creating high-intensity acoustic beams converging 6 mm away at a 16 MHz frequency. Cell lysis is achieved through centrifugal forces acting on Candida albicans cells and glass particles within the focal area. To optimize this SAW-induced streaming, we conducted 42 pilot experiments, varying electrical power, droplet volume, glass particle size, concentration, and lysis time, resulting in optimal conditions: an electrical signal of 2.5 W, a 20 μL sample volume, glass particle size below 10 μm, concentration of 0.2 μg, and a 5-min lysis period. We successfully amplified DNA target fragments directly from the lysate, demonstrating an efficient microchip-based cell lysis method. When combined with an isothermal amplification technique, this technology holds promise for rapid point-of-care (POC) applications.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; MÜHENDİSLİK, ÇEVRE; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; MICROBIOLOGY; ENGINEERING, ENVIRONMENTAL; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Çevre Mühendisliği; Bioengineering; Physical Sciences; Environmental Engineering; cell lysis; droplet; micro-glass particle; surface acoustic wave